Proton Exchange Membrane Fuel Cell Parameter Extraction Using a Supply–Demand-Based Optimization Algorithm - Abdullrahman A. Al-Shamma’a (Processes, 2021)
For proton exchange membrane fuel cells (PEMFCs), the parameter extraction issue is among the most widely studied problems in the field of energy storage systems, since the precise identification of such parameters plays an important role in increasing the PEMFC performance and life span. The optimization process is intended to adjust the performance of PEMFCs by appraising the optimal parameters that produce a good estimation of the current–voltage (I–V) curve. In order to build an accurate equivalent circuit model for PEMFCs, a reliable and effective parameter extraction algorithm, termed a supply–demand-based optimization (SDO) algorithm, is proposed in this paper. Nine parameters (<semantics>ξ1, ξ2, ξ3, ξ4, Rc, β, λ, l, and Jmax</semantics>) are evaluated, to minimize the sum squared deviation (SSE) between the experimental and simulated I–V curves. To validate the feasibility and effectiveness of the SDO algorithm, four sets of experimental data with diverse characteristics and two well-known PEMFC stacks (BSC500W and 500W Horizon) are employed. Comparison of the simulated and experimental results clearly demonstrates the superiority/competitiveness of the SDO algorithm over five well-established parameter extraction algorithms, i.e., the whale optimization algorithm (WOA), grey wolf optimization (GWO), Harris hawks optimization (HHO), and genetic algorithm (GA). Several evaluation criteria, including best SSE, worst SSE, mean SSE, and standard deviation, show that the SDO algorithm has merits in terms of PEMFC modeling.